USING ‘BECAUSE YOU LOVED ME’ SONG TO TEACH PAST SIMPLE IN EFL CLASSROOMS - Asfi Aniuranti; Putri Amalia Rizkina (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
This study was aimed at investigating the effectiveness of an English song entitled ‘Because You Loved Me’ to teach past simple. Past simple itself is oneof the necessary yet problematic tenses for learners. The research employed was quasi-experimental pretest-post-test design was employed in this research. Thepopulation of this study was five classes of the first grade students of senior highschool. Due to the high number of the population, this research only used twoclasses as the sampling - one class as the experimental group and the other oneas the control group. This research was carried out through four stages namelypretest, treatment implementation, post-test and data analysis. The result of thedata analysis showed that ‘Because You Loved Me’ song is effective for teachingpast simple. The value of t-test was higher than the t-table. The result of t-test formula was 1.91, and the t-table was 1.67. Overall, English song entitled ‘Because You Loved Me’ is effective to teach past simple and using songs in EFLclassrooms may also provide comfortable and interesting teaching and learningprocess.